Effects of Gintonin-Enriched Fraction in an Atopic Dermatitis Animal Model: Involvement of Autotaxin Regulation - Lee, Byung-Hwan; Kim, Ho-Kyoung; Jang, Minhee; Kim, Hyeon-Joong; Choi, Sun-Hye; Hwang, Sung-Hee; Kim, Hyoung-Chun; Rhim, Hyewhon; Cho, Ik-Hyun; Nah, Seung-Yeol (PHARMACEUTICAL SOC JAPAN, 2017)
Ginseng extract has been used for prevention of atopic dermatitis (AD) in experimental animal models. However, little is known about its active ingredients and the molecular mechanisms underlying its anti-AD effects. Recently, we isolated a unique lysophosphatidic acid (LPA) receptor ligand, gintonin, from ginseng. Gintonin, the glycolipoprotein fraction of ginseng, contains LPAs, mainly LPA C-18:2 with other minor lysophospholipid components. A line of evidence showed that serum autotaxin (ATX) activity and level are significantly elevated in human AD patients compared to those in normal controls, which indicates that ATX may be involved in human AD. In a previous study, we demonstrated that gintonin exerted anti-inflammatory effects via inhibition of microglial activation and proinflammatory cytokine production by immune cells and that it strongly inhibited ATX activity. In this study, we investigated whether oral administration of the gintonin-enriched fraction (GEF) could ameliorate the symptoms of 2,4-dinitrofluorobenzene (DNFB)-induced AD in NC/Nga mice. We found that oral administration of GEF to DNFB-induced AD mice for 2 weeks reduced ear swelling and AD skin index. In addition, oral administration of GEF reduced the serum levels of immunoglobulin E, histamine, interleukin-4, and interferon-gamma. Histological examination showed that oral administration of GEF attenuated skin inflammation and significantly reduced eosinophil and mast cell infiltration into the skin. Moreover, oral administration of GEF not only decreased serum ATX level but also reduced serum ATX activity. The present study shows that the anti-AD effects of ginseng might be attributed to GEF-induced anti-inflammatory activity and ATX regulation.
Keywords: LYSOPHOSPHOLIPASE-D-ACTIVITY; RED GINSENG EXTRACT; LYSOPHOSPHATIDIC ACID; NC/NGA MICE; INFLAMMATION; PRURITUS; LESIONS; CELLS